The helminth product ES-62 protects against septic shock via Toll-like receptor 4-dependent autophagosomal degradation of the adaptor MyD88 - Puneet, P.; McGrath, M.; Tay, H.; Al-Riyami, L.; Rzepecka, J.; Moochhala, S.; Pervaiz, Shazib; Harnett, M.; Harnett, W.; Melendez, A. (Nature Publishing Group, 2011)
Sepsis is one of the most challenging health problems worldwide. Here we found that phagocytes from patients with sepsis had considerable upregulation of Toll-like receptor 4 (TLR4) and TLR2; however, shock-inducing inflammatory responses mediated by these TLRs were inhibited by ES-62, an immunomodulator secreted by the filarial nematode Acanthocheilonema viteae. ES-62 subverted TLR4 signaling to block TLR2- and TLR4-driven inflammatory responses via autophagosome-mediated downregulation of the TLR adaptor-transducer MyD88. In vivo, ES-62 protected mice against endotoxic and polymicrobial septic shock by TLR4-mediated induction of autophagy and was protective even when administered after the induction of sepsis. Given that the treatments for septic shock at present are inadequate, the autophagy-dependent mechanism of action by ES-62 might form the basis for urgently needed therapeutic intervention against this life-threatening condition. © 2011 Nature America, Inc. All rights reserved.